An Evaluative Study of System Model/Approach in Private University Education System in India for Quality and Effective Education System - Singh, Sumit Kumar; Ramaswamy , Chandramohan; Sanker , C. N. Prabhu (Recent Advances in Commerce, Management, and Tourism, 2023)
In India, the higher education system is comprised of both public and private universities. While public universities receive financial support from the government, whereas private universities are primarily getting financial support by various societies and organizations. Public universities adhere to the education system model established by either the central or state government, whereas private universities have their own unique education system models which vary by institution. The UGC or AICTE regulate higher education, so most functions and procedures are similar, but the quality and quantity differ. The primary difference between private and public universities is the funding arrangements for operating the institution. Public universities receive most of their funding from the central or state government, while private universities must arrange their own funding. Despite facing challenges in fundraising, private universities have more opportunities to experiment with their education system models. This paper aims to develop an effective education system model for private universities by evaluating related research papers & reports and presenting the results in form of a conceptual paper.